Khashoggi Case and the Issue of Human Rights Protectionof Journalists - Apriliyanto, Migel; Yasa, Made Maharta (Kertha Patrika; Vol 40 No 3 (2018)DO - 10.24843/KP.2018.v40.i03.p01, 2018)
Jamal Khashoggi is known for his very sharp critics to Saudi Arabian Governments. He wa s murdered at the Consulate facility of Saudi Arabia in Istanbul - Turkey. The case has become a concern of international society, put the questions of freedom of expression and press as well the security of journalist. This article is a normative legal research that is aimed to analyze the international human rights law ’s protection to the journalist's activities and to discuss the case of Khashoggi, specifically on the issue which authorities that have obligations to impose legal sanctions to the alleged perpetrators. The research suggests that there have been international human rights norms and principles that protect journalist activities. In addition, it suggests that Turkey has jurisdiction to launch an investigation and prosecute the perpetrators who involve in the murder of Jamal Khashoggi.